ANALISIS KINERJA KEUANGAN BERDASARKAN CASH RATIO, LOAN TO DEPOSIT RATIO, GROSS PROFIT MARGIN, DAN RETURN ON EQUITY RATIO PADA PT BANK DANAMON INDONESIA TBK - Radiatun Radiatun (Politeknik Bisnis Indonesia, 2022)
The purpose of this study is to determine the condition of the liquidity ratio and profitability ratio baset on the cash ratio variable, loan to deposit ratio, how the condition of the profitability ratio basedon the gross profit margn variable, retuen on equity ratio at PT Bank Danamon indonesia, Tbk during 2011-2020. The type of research used in this research is descriptive reseach using a quantitative approach, the data used in this study was obtained from the annual report published by PT Bank Danamon Indonesia, TBK during the years 2011-2020. Data collection techniques used are documentation study techniques, data analysis techniques used are liquidity ratio analysis, profitability ratio. The reults of this study show that financial performance conditions based on liquidity ratio (cash ratio and loan to deposito ratio) show very good conditions, profitability ratio (gross profit margin and return on equity ratio) show good conditions.